In-situ grown TiO2 nanorod loaded single-layer Ir atom catalyst as well as preparation method and application thereof
By growing monolayer Ir atoms in situ on the surface of TiO2 nanorods to form a TiO2 nanorod supported monolayer Ir atom catalyst, the problem of difficulty in achieving both activity and stability in the process of acidic electrolysis of oxygen, achieving efficient and stable electrocatalytic performance.
Patent Information
- Application Number
- CN202311327120.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2025-04-15
AI Technical Summary
During the existing process of acidic electrolytic oxygen analysis, the atomic utilization rate of noble metal Ir-based catalysts is low, and it is difficult to achieve both stability and activity under acidic conditions.
The TiO2 nanorods are formed by growing TiO2 nanorods in situ on a conductive substrate and loading a single layer of Ir atoms on their surface. This method achieves high dispersion and stable loading of Ir atoms through hydrothermal reaction and subsequent calcination steps.
The electrocatalytic activity and stability of the catalyst were improved, the amount of precious metals was reduced, the preparation cost was reduced, and the operation was stable at a flow density of 10mA/cm2 for 109 hours, and the morphological structure did not change significantly.
Smart Images

Figure CN119824473A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalysts, and in particular to an in-situ grown TiO 2 Nanorod-loaded single-layer Ir atom catalyst, preparation method and application thereof. Background Art
[0002] In recent years, energy shortage and environmental pollution have become two major problems affecting the sustainable development of human society. The integration of renewable energy and water electrolysis hydrogen production technology to produce "green hydrogen" can achieve zero carbon emissions and provide a sustainable energy storage strategy. Among various water electrolysis hydrogen production technologies, proton exchange membrane (PEM) water electrolysis technology, which has the advantages of low resistance loss, high current density and high energy efficiency, is highly favored and has become a hot topic in current research. However, its development is restricted by factors such as high catalytic overpotential of the anodic oxygen evolution reaction, low water electrolysis efficiency (a four-electron process with slow kinetics) and poor stability of the catalyst in acidic solution. At present, the anode catalyst is mainly based on relatively stable but low catalytic activity, expensive and scarce precious metal Ir-based materials, which limits its large-scale application. Therefore, the development of acidic OER catalysts with high activity, low precious metal loading and high stability is a major challenge in the field of water electrolysis. Studies have shown that single-atom catalysts with theoretically 100% metal dispersion on the carrier surface can effectively improve the atomic utilization rate, reduce the amount of precious metal elements, and improve the activity of the catalyst. However, this type of precious metal single-atom catalyst has problems such as low loading rate, difficulty in preparation, poor stability, easy agglomeration and shedding, which ultimately lead to catalyst deactivation. Summary of the invention
[0003] The present invention provides an in-situ grown TiO 2 Nanorod-loaded single-layer Ir atom catalyst, preparation method and application thereof.
[0004] To achieve the above objectives, the present invention provides an in-situ grown TiO 2 Nanorods support a single layer of Ir atoms, where the TiO2 is grown on a conductive substrate. 2 The nanorods are loaded with a layer of Ir atoms dispersed in atomic form.
[0005] According to the present invention, Ir atoms in the Ir atomic layer are arranged along the TiO 2 The Ti sites in the MgCl2O3 are arranged periodically.
[0006] According to the present invention, the substrate can be selected from carbon fiber, carbon paper, conductive glass, in particular a carbon substrate.
[0007] According to the present invention, TiO grown on a conductive substrate 2 Including rutile TiO 2 and anatase TiO 2 .
[0008] Another aspect of the present invention provides an in-situ grown TiO 2 The preparation method of a nanorod-supported monolayer Ir atom catalyst comprises:
[0009] (1)TiO 2 Preparation of nanorods:
[0010] First, the titanate is dissolved in alcohol, and then the conductive substrate is immersed in the alcohol solution of the titanate, taken out, dried, and calcined for the first time in an air atmosphere to obtain TiO 2 Seed layer;
[0011] Next, the TiO 2 The substrate of the seed layer is placed in a reactor containing titanate and acid, and then a hydrothermal reaction is carried out. After the reaction is completed, it is naturally cooled to room temperature, washed and dried, and then calcined for the second time to obtain uniformly grown TiO 2 Nanorod carrier; (2) TiO 2 Preparation of nanorod-supported monolayer Ir atom catalyst:
[0012] The TiO prepared in step (1) 2 The nanorods were immersed in a 1-7 mg / mL chloroiridic acid alcohol solution, and the TiO 2 The nanorods are dried and calcined at 200-450 °C in an inert atmosphere to obtain TiO 2 Nanorod-supported monolayer Ir atom catalyst.
[0013] According to the present invention, in step (1),
[0014] In particular,
[0015] The conductive substrate is immersed in the alcohol solution of titanate for 1-10 minutes; and / or
[0016] The titanate is selected from butyl titanate, titanium isopropoxide, titanium tetrachloride, titanium sulfate; the alcohol is selected from isopropanol, ethanol, methanol; and / or
[0017] The volume ratio of titanate to alcohol is 1:30-50, for example 1:40; and / or
[0018] The conductive substrate is selected from carbon fiber, carbon paper, conductive glass; and / or
[0019] The first calcination is carried out at 300-500°C for 2-4h; and / or
[0020] The acid is hydrochloric acid, the concentration of the acid is 3-6M, and the volume ratio of the titanate to the hydrochloric acid is 1:90-120, for example 1:100; and / or
[0021] The reactor may be a polytetrafluoroethylene reactor; and / or
[0022] The hydrothermal reaction may be carried out at 140-180° C. for 6-12 hours; and / or
[0023] The second calcination is carried out at 300-500°C for 2-4h; and / or
[0024] The second calcination is not limited to an atmosphere, and can be carried out in an atmosphere selected from air atmosphere, hydrogen and argon atmosphere, inert atmosphere, and the like.
[0025] According to the present invention, in step (2),
[0026] In particular,
[0027] The concentration of chloroiridic acid is 1 to 5 mg / mL; and / or
[0028] TiO 2 The nanorods are placed in the chloroiridic acid alcohol solution for 3 to 5 hours; and / or
[0029] Calcination under an inert atmosphere for 2-4 hours; and / or
[0030] The inert atmosphere is a nitrogen atmosphere, an argon atmosphere, a helium atmosphere or a mixed atmosphere thereof.
[0031] According to one embodiment of the present invention, the method comprises:
[0032] (1)TiO 2 Preparation of nanorods:
[0033] First, butyl titanate is dissolved in isopropanol, and then the carbon fiber substrate is immersed in the above mixture for 1-10 minutes, taken out, dried, and then calcined for the first time at 300-500℃ in air atmosphere for 2-4 hours to obtain TiO 2 Seed layer;
[0034] Next, the TiO 2 The carbon fiber substrate of the seed layer is placed in a polytetrafluoroethylene reactor containing a mixture of butyl titanate and 3-6M hydrochloric acid, and then subjected to a hydrothermal reaction at 150-180°C for 8-10 hours. After the reaction is completed, it is naturally cooled to room temperature, washed and dried, and then calcined for a second time at 300-500°C in air for 2-4 hours to obtain uniformly grown TiO 2 Nanorod carrier;
[0035] (2)TiO 2Preparation of nanorod-supported monolayer Ir atom catalyst:
[0036] The TiO prepared in step (1) 2 The nanorods were immersed in 1-7 mg / mL chloroiridic acid ethanol solution for 3-5 h, and then the TiO 2 The nanorods are dried and calcined at 200-450 °C for 2-4 h in an inert atmosphere to obtain TiO 2 Nanorod-supported monolayer Ir atom catalyst.
[0037] In the above preparation method, preferably, in step (1),
[0038] The volume ratio of butyl titanate to isopropyl alcohol may be 1:30-50, for example 1:40; and / or
[0039] The first calcination temperature is 400-500°C; and / or
[0040] The hydrochloric acid concentration is 3-6M; and / or
[0041] The volume ratio of butyl titanate to hydrochloric acid is 1:90-120, for example 1:100; and / or
[0042] The second calcination temperature is 400-500°C.
[0043] In the above preparation method, preferably, in step (2),
[0044] The concentration of chloroiridic acid is 1 to 5 mg / mL; and / or
[0045] The immersion time is 3 to 4 hours; and / or
[0046] The calcination temperature is 300-400° C.; and / or
[0047] The inert atmosphere is nitrogen, argon, helium or a mixed atmosphere thereof.
[0048] According to another aspect of the present invention, there is provided the TiO 2 Application of nanorod-supported monolayer Ir atom catalysts in electrocatalytic oxygen evolution reaction under acidic conditions.
[0049] The present invention adopts the method of 2 A continuous monolayer of Ir atoms was successfully loaded on the surface of the nanorods, which showed excellent electrocatalytic activity and stability. 2Compared with nanoparticles, the monolayer Ir atoms can expose more active sites, reduce the amount of precious metals, and reduce the cost of catalyst preparation; compared with single-atom catalysts, the monolayer Ir atoms not only maintain the advantage of 100% atomic utilization of single atoms, but also have multiple continuous metal active sites, while improving the total current density of the material; the catalyst prepared by the present invention has excellent stability, and the current density is 10mA / cm 2 After running stably for 109 hours at a flow density, its morphology and structure did not change significantly. The present invention adopts an in-situ growth method to make the catalyst and the substrate closely bonded, promote electron transfer, effectively improve the catalytic reaction kinetics, and reduce the contact resistance between the conventional powder catalyst and the substrate. The catalyst preparation method of the present invention is simple, low-cost, can be prepared on a large scale, and has potential industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 The TiO prepared in Example 1 2 Nanorod-supported single-layer Ir atom catalyst and TiO prepared in Comparative Example 1 2 XRD pattern of nanorod-supported Ir single-atom catalyst.
[0051] Figure 2 (a, b) are TiO prepared in Comparative Example 3 2 SEM images of nanorods at different magnifications. Figure 2 (c, d) are TiO prepared in Example 1 2 SEM images of the single-layer Ir atomic catalyst supported on nanorods at different magnifications.
[0052] Figure 3 The TiO prepared in Example 1 2 STEM image of a single-layer Ir atom catalyst supported by nanorods, where Figure 3 Figures ad show HAADF-STEM images at different magnifications. Figure 3 d is Figure 3 c is the enlarged picture of the frame part. Figure 3 Figure e shows the HAADF signal analysis result.
[0053] Figure 4 The TiO prepared in Example 2 2 STEM image and mapping image of the single-layer Ir atom catalyst supported by nanorods, where Figure 4 Figures ac show the TiO 2 STEM image of the Ir atomic layer loaded on the surface of the nanorod carrier. Figure 4 d shows the EDS analysis results.
[0054] Figure 5 The TiO prepared in Comparative Example 12 STEM image of nanorod-supported Ir single-atom catalyst.
[0055] Figure 6 The LSV curves of the catalysts prepared in Examples 1, 2, 3 and 4 are shown in FIG.
[0056] Figure 7 It is an LSV curve diagram of the catalyst test prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4.
[0057] Figure 8 This is a graph showing the stability test results of the catalysts prepared in Comparative Example 1 and Example 1.
[0058] Fig. 9 This is a STEM image of the catalyst prepared in Example 1 after stability testing. DETAILED DESCRIPTION
[0059] The present invention is further described below in conjunction with embodiments. The examples listed are only used to explain the present invention and are not intended to limit the scope of the present invention.
[0060] Unless otherwise specified, the raw materials, reagents, equipment, etc. required in the following examples and comparative examples are all commercially available.
[0061] Test equipment and methods:
[0062] The XRD test was carried out on a PANalytical X'Pert PRO XRD analyzer using Cu Kα radiation, a wavelength of λ=0.1542 nm, and a scanning speed of 5° / min.
[0063] SEM was performed on a Hitachi SU-8010 instrument.
[0064] HAADF-STEM was tested on a Themis Z instrument with an accelerating voltage of 200 kV.
[0065] The LSV polarization curve test was carried out in a three-electrode system using a Shanghai Chenhua CHI660E electrochemical workstation with a scan rate of 5 mV / s. -1 The test voltage range is 1-1.8V, and all electrode potentials in the polarization curves are corrected by manual iR compensation.
[0066] The stability test is carried out by testing a certain current density (10mA / cm 2 and 80mA / cm 2 ) The voltage changes with time and whether the voltage changes significantly within a certain period of time is observed to evaluate the stability of the catalyst.
[0067] In the present invention, the hydrogen-argon atmosphere refers to a mixed atmosphere of hydrogen and argon, wherein the volume fraction of hydrogen is preferably 5%-10%, and the volume fraction of argon is preferably 90%-95%.
[0068] Example 1
[0069] (1)TiO 2 Preparation of nanorods: First, TiO was prepared on a carbon fiber substrate (Taiwan Carbon Energy Carbon Cloth, WOS 1011). 2 The seed layer comprises the following steps: dissolving butyl titanate in isopropanol (the volume ratio of butyl titanate to isopropanol is 1:40), then immersing the carbon fiber substrate in the above-mentioned mixed solution for 2 minutes, taking it out, drying it, and then heating it to 400°C at a heating rate of 2°C / min, and calcining it in an air atmosphere for 2 hours to obtain TiO 2 Seed layer.
[0070] Next, the TiO 2 The carbon fiber substrate of the seed layer was placed in a polytetrafluoroethylene reactor containing a mixture of butyl titanate and 6M hydrochloric acid (the volume ratio of butyl titanate to hydrochloric acid was 1:100), and then hydrothermally reacted at 150°C for 8 hours. After the reaction was completed, it was naturally cooled to room temperature, washed and dried; it was further heated to 400°C and calcined at this temperature in an air atmosphere for 2 hours to obtain uniformly grown TiO 2 Nanorod carrier.
[0071] (2)TiO 2 Preparation of nanorod-supported monolayer Ir atom catalyst: TiO prepared in step (1) 2 The nanorods were immersed in 3 mg / mL chloroiridic acid ethanol solution for 4 h, and the TiO 2 The nanorods were dried and calcined at 300 °C for 2 h in an argon atmosphere to obtain TiO 2 Nanorod-supported monolayer Ir atom catalyst.
[0072] Figure 1 The TiO prepared in Example 1 is shown 2 The XRD pattern of the nanorod-supported single-layer Ir atom catalyst, compared with the standard diffraction pattern, shows that the TiO prepared in Example 1 2 Nanorods TiO 2 The nanorod-supported monolayer Ir atom catalysts include rutile phase (mainly, JCPD#21-1276) and anatase phase (JCPD#21-1272) TiO 2 , and no characteristic diffraction peak related to Ir was found in the spectrum, indicating that Ir is highly dispersed in the catalyst.
[0073] Figure 2 c and d show the TiO prepared in Example 1. 2 SEM image of a single-layer Ir atom catalyst supported by nanorods. As shown in the figure, the diameter of the TiO nanorods is 50-100 nm and the length is about 2 μm. 2 The nanorods were uniformly grown on the carbon cloth substrate, which was similar to the pure TiO prepared in Comparative Example 3. 2 SEM images of nanorods ( Figure 2 Compared with (a, b), TiO 2 The morphology of the nanorods remained unchanged.
[0074] Figure 3 The TiO prepared in Example 1 is shown 2 HAADF-STEM images of a single-layer Ir atomic catalyst supported by nanorods. From the HAADF-STEM images at different magnifications in the figure, it can be seen that evenly spaced bright spots form a regular arrangement in the catalyst, indicating that continuous Ir atomic layers grow evenly on the TiO 2 Nanorod surface; further Figure 3 The HAADF signal analysis of e shows that the atomic distance of Ir-O-Ir is Theoretical interatomic distance of Ti-O-Ti This matches the results, indicating that the Ir atomic layer is along the TiO 2 The Ti sites in the MgCl2O3 are arranged periodically.
[0075] Example 2
[0076] (1)TiO 2 Preparation of nanorods: proceed as in Example 1.
[0077] (2)TiO 2 Preparation of nanorod-supported monolayer Ir atom catalyst: TiO prepared in step (1) 2 The nanorods were immersed in 1 mg / mL chloroiridic acid ethanol solution for 4 h, and the TiO 2 The nanorods were dried and calcined at 300 °C in an argon atmosphere for 2 h to obtain TiO 2 Nanorod-supported monolayer Ir atom catalyst.
[0078] Figure 4 The TiO prepared in Example 2 is shown 2 STEM images and mapping images of the single-layer Ir atomic catalyst supported by nanorods, such as Figure 4 As shown in Fig. ac, the Ir atomic layer is successfully loaded on the TiO 2 Nanorod support surface; Figure 4 The EDS elemental distribution of d confirms the high dispersion of Ir, and the local dense signals correspond to the continuous array of Ir atoms.
[0079] Example 3
[0080] (1)TiO 2 Preparation of nanorods: proceed as in Example 1.
[0081] (2)TiO 2 Preparation of nanorod-supported monolayer Ir atom catalyst: TiO prepared in step (1) 2 The nanorods were immersed in 2 mg / mL chloroiridic acid ethanol solution for 4 h, and the TiO 2 The nanorods were dried and calcined at 300 °C for 2 h in an argon atmosphere to obtain TiO 2 Nanorod-supported monolayer Ir atom catalyst.
[0082] Example 4
[0083] (1)TiO 2 Preparation of nanorods: proceed as in Example 1.
[0084] (2)TiO 2 Preparation of nanorod-supported monolayer Ir atom catalyst: TiO prepared in step (1) 2 The nanorods were immersed in 3 mg / mL chloroiridic acid ethanol solution for 3 h, and the TiO 2 The nanorods were dried and calcined at 400 °C for 2 h in a nitrogen atmosphere to obtain TiO 2 Nanorod-supported monolayer Ir atom catalyst.
[0085] Comparative Example 1
[0086] (1)TiO 2 Preparation of nanorods: proceed as in Example 1.
[0087] (2)TiO 2 Preparation of nanorod-supported Ir single-atom catalyst: TiO prepared in step (1) 2 The nanorods were immersed in 0.25 mg / mL chloroiridic acid ethanol solution for 4 h, and the TiO 2 The nanorods were dried and calcined at 300 °C for 2 h in an argon atmosphere to obtain TiO 2 Nanorod-supported Ir single-atom catalysts.
[0088] Figure 5 The TiO prepared in Comparative Example 1 is shown. 2 STEM image of nanorod-supported Ir single-atom catalyst, such as Figure 5 As shown, independent Ir atoms (bright spots) are randomly distributed on the TiO 2Nanorods on carrier.
[0089] Comparative Example 2
[0090] (1)TiO 2 Preparation of nanorods: proceed as in Example 1.
[0091] (2)TiO 2 Preparation of nanorod-supported Ir nanoparticle catalyst: TiO 2 The nanorods were immersed in 3 mg / mL chloroiridic acid ethanol solution for 4 h, and the TiO 2 The nanorods were dried and calcined at 500 °C for 2 h in an argon atmosphere to obtain TiO 2 Nanorods supported Ir nanoparticle catalyst.
[0092] Comparative Example 3
[0093] TiO was prepared according to step (1) of Example 1. 2 Nanorods.
[0094] Comparative Example 4
[0095] Commercial IrO produced by Henan Zijing 2 Catalyst (model 12030-49-8), catalyst loading 40 μg Ir / cm 2 .
[0096] Test example:
[0097] The electrocatalytic oxygen production performance test method of all embodiments and comparative examples is as follows: in an environment of 23-25°C, using Chenhua CHI660E workstation, a three-electrode system test is adopted, wherein the Ag / AgCl electrode is the reference electrode, the platinum sheet is the counter electrode, the working electrode test area is 1×1 cm, and the electrolyte is 0.1M HClO 4 Solution, linear scan rate is 5mV / s.
[0098] Figure 6 The LSV polarization curves of the catalysts prepared in Example 1, Example 2, Example 3 and Example 4 are shown.
[0099] Figure 7 The LSV curves of the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are shown.
[0100] The catalysts of the examples and comparative examples were 2 The overpotentials at the current density as well as the current density and mass activity at a voltage of 1.53 V are shown in Table 1.
[0101] Table 1
[0102]
[0103] The above examples show that: compared with the commercial IrO 2 Compared with the catalyst, the TiO 2 Nanorod-loaded Ir atomic layer catalysts (Examples 1, 2, and 3) are used as catalysts for oxygen production by electrolysis of water under acidic conditions. They have low oxygen evolution overpotential, high mass activity, and good oxygen evolution catalytic performance at a current density of 10 mA cm -2 The overpotential (<300mV) is significantly lower than that of commercial IrO 2 The mass activity of the catalyst (Comparative Example 4) at a potential of 1.53 V is 373 mV, which is comparable to that of commercial IrO 2 Compared with the Ir single atom catalyst of Comparative Example 1, the mass activity and geometric activity (low overpotential) of each example are better than the single atom catalyst, and the total current density is also higher ( Figure 6 and Figure 7 ), indicating that TiO 2 The monolayer Ir atoms loaded on the surface of the nanorods not only maintain the high activity of the single atoms, but also further enhance the OER activity of the catalyst due to the interaction between the Ir atoms, and enhance the total current density of the oxygen evolution reaction without sacrificing the exposed active sites. Compared with the Ir nanoparticle catalyst of Comparative Example 2, the overpotential of the catalysts of each example is significantly reduced, and the mass activity is significantly improved, indicating that the monolayer Ir atoms can expose more effective active sites than nanoparticles.
[0104] Figure 8 The OER stability of the Ir atomic layer catalyst prepared in Example 1 and the Ir single atom catalyst prepared in Comparative Example 1 is shown. By comparing the Ir single atom and Ir atomic layer catalysts at a current density of 10 mA cm -2 It can be seen from the constant current test (CP) at that the overpotential of the Ir atomic layer catalyst (Example 1) increased by only 50 mV after continuous operation for 109 h, and the STEM image after the stability test ( Fig. 9 ) shows that its single atomic layer structure remains unchanged, indicating that the Ir atomic layer catalyst has excellent stability; while the OER activity of the Ir single atom catalyst (Comparative Example 1) has completely decayed after running for 10 hours. In addition, the inventors also -2 ) was used to test the stability of the Ir atomic layer catalyst (Example 1), and it was found that after continuous operation for 100 h, its overpotential increased by less than 100 mV, further indicating that the TiO prepared by the present invention 2The nanorod-supported monolayer Ir atom catalyst (Example 1) has excellent stability and has potential industrial application prospects.
[0105] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. An in-situ grown TiO2 nanorod-supported monolayer Ir atom catalyst, wherein: A layer of Ir atoms dispersed in atomic form is loaded on the TiO2 nanorods grown on a conductive substrate.
2. The in-situ grown TiO2 nanorod-supported monolayer Ir atom catalyst according to claim 1, wherein: The substrate is selected from carbon fiber, carbon paper, and conductive glass.
3. The in-situ grown TiO2 nanorod-supported monolayer Ir atom catalyst according to claim 1 or 2, wherein: The Ir atoms in the Ir atomic layer are arranged periodically along the Ti sites of TiO2.
4. A method for preparing an in-situ grown TiO2 nanorod-supported monolayer Ir atom catalyst, comprising: (1) Preparation of TiO2 nanorods: Firstly, dissolving titanate in alcohol, then immersing the conductive substrate in the alcohol solution of titanate, taking out, drying, and performing a first calcination in an air atmosphere to obtain a TiO2 seed layer; Next, the substrate on which the TiO2 seed layer is grown is placed in a reactor containing titanate and acid, and then a hydrothermal reaction is carried out. After the reaction is completed, the substrate is naturally cooled to room temperature, washed and dried, and then calcined for the second time to obtain a uniformly grown TiO2 nanorod carrier. (2) Preparation of TiO2 nanorods loaded with monolayer Ir atom catalyst: The TiO2 nanorods prepared in step (1) are immersed in a 1-7 mg / mL chloroiridic acid alcohol solution, the TiO2 nanorods rich in the immersion solution are taken out, dried, and calcined at 200-450°C in an inert atmosphere to obtain a single-layer Ir atomic catalyst loaded on the TiO2 nanorods.
5. The preparation method according to claim 4, wherein In step (1), The conductive substrate is immersed in the alcohol solution of titanate for 1-10 minutes; and / or The titanate is selected from butyl titanate, titanium isopropoxide, titanium tetrachloride, titanium sulfate; the alcohol is selected from isopropanol, ethanol, methanol; and / or The volume ratio of titanate to alcohol is 1:30-50; and / or The conductive substrate is selected from carbon fiber, carbon paper, conductive glass; and / or The first calcination is carried out at 300-500°C for 2-4h; and / or The acid is hydrochloric acid, the concentration of the acid is 3-6M, and the volume ratio of titanate to acid is 1:90-120; and / or The reactor is a polytetrafluoroethylene reactor; and / or The hydrothermal reaction is carried out at 140-180° C. for 6-12 hours; and / or The second calcination is carried out at 300-500°C for 2-4h; and / or The second calcination is carried out in an atmosphere selected from air, hydrogen and argon, and an inert atmosphere.
6. The preparation method according to claim 4 or 5, wherein: In step (2), The concentration of chloroiridic acid is 1 to 5 mg / mL; and / or The TiO2 nanorods are placed in the chloroiridic acid alcohol solution for 3 to 5 hours; and / or Calcination under an inert atmosphere for 2-4 hours; and / or The inert atmosphere is a nitrogen atmosphere, an argon atmosphere, a helium atmosphere or a mixed atmosphere thereof.
7. The preparation method according to claim 4, wherein The method comprises: (1) Preparation of TiO2 nanorods: First, dissolve butyl titanate in isopropanol, then immerse the carbon fiber substrate in the mixed solution for 1-10 minutes, take it out, dry it, and then calcine it for the first time in an air atmosphere at 300-500°C for 2-4 hours to obtain a TiO2 seed layer; Next, the carbon fiber substrate with the TiO2 seed layer grown thereon is placed in a polytetrafluoroethylene reactor containing a mixture of butyl titanate and 3-6M hydrochloric acid, and then subjected to a hydrothermal reaction at 150-180°C for 8-10 hours. After the reaction is completed, the substrate is naturally cooled to room temperature, washed and dried, and then calcined for a second time at 300-500°C in air for 2-4 hours to obtain a uniformly grown TiO2 nanorod carrier. (2) Preparation of TiO2 nanorods loaded with monolayer Ir atom catalyst: The TiO2 nanorods prepared in step (1) are immersed in a 1-7 mg / mL chloroiridic acid ethanol solution, and after standing for 3-5 hours, the TiO2 nanorods rich in the impregnation solution are taken out, dried, and calcined at 200-450°C in an inert atmosphere for 2-4 hours to obtain a single-layer Ir atomic catalyst loaded on the TiO2 nanorods.
8. The preparation method according to claim 7, wherein: In step (1), The volume ratio of butyl titanate to isopropyl alcohol may be 1:30-50, for example 1:40; and / or The first calcination temperature is 400-500°C; and / or The hydrochloric acid concentration is 3-6M; and / or The volume ratio of butyl titanate to hydrochloric acid is 1:90-120, for example 1:100; and / or The second calcination temperature is 400-500°C.
9. The preparation method according to claim 7 or 8, wherein: In step (2), The concentration of chloroiridic acid is 1 to 5 mg / mL; and / or The immersion time is 3 to 4 hours; and / or The calcination temperature is 300-400° C.; and / or The inert atmosphere is nitrogen, argon, helium or a mixed atmosphere thereof.
10. Use of the TiO2 nanorod-supported monolayer Ir atomic catalyst according to any one of claims 1 to 3 or the in-situ grown TiO2 nanorod-supported monolayer Ir atomic catalyst prepared by the preparation method according to any one of claims 4 to 9 in electrocatalytic oxygen evolution reaction under acidic conditions.